Determination of Acquisition Frequency for Intrafractional Motion of Pancreas in CyberKnife Radiotherapy. (13th May 2014) - Zhang, Huailing; Zhao, Guoru; Djajaputra, David; Xie, Yaoqin
Abstract : Purpose. To report the characteristics of pancreas motion as tracked using implanted fiducials during radiotherapy treatments with CyberKnife. Methods and Materials . Twenty-nine patients with pancreas cancer treated using CyberKnife system were retrospectively selected for this study. During the treatment, the deviation is examined every 3-4 nodes (~45 s interval) and compensated by the robot. The pancreas displacement calculated from X-ray images acquired within the time interval between two consecutive couch motions constitute a data set. Results . A total of 498 data sets and 4302 time stamps of X-ray images were analyzed in this study. The average duration for each data set is 634 s. The location of the pancreas becomes more dispersed as the time elapses. The acquisition frequency depends on the prespecified movement distance threshold of pancreas. If the threshold between two consecutive images is 1 mm, the acquisition frequency should be less than 30 s, while if the threshold is 2 mm, the acquisition frequency can be around 1 min. Conclusions . The pancreas target moves significantly and unpredictably during treatment. Effective means of compensating the intrafractional movement is critical to ensure adequate dose coverage of the tumor target.